The procedural legal business and the promise not to sue (Research, Society and Development, 2021)
The pactum de non petendo in spite of not being a new institute gains a new approach in face of the current procedural approach. As a result of the Criminal Organizations Law and the non-criminal prosecution agreement, the issue has also become relevant to civil proceedings. The objective is to briefly expose the concepts of legal fact and legal transaction, together with specific principles that govern the pactum de non petendo. The problematization is found in the possibility or not of the parties to agree on a promise not to sue as a means of assisting the consensual cooperative perspective of conflict resolution. For this purpose, bibliographic analysis is used as a methodology, especially by the author Alberto Trigo, in addition to the relevant legislation.